Hashitoxicosis: A Case Report - Dhini Sylvana; Dharma Lindarto; Santi Syafril; Melati Silvanni Nasution; Dian Anindita Lubis; Stephen Udjung (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Hashimoto Thyroiditis with Grave’s disease/Hashitixicosis is found in some cases, snd this case repirt describes a case of a woman with Hashitoxicosis. A 27 year old woman came to polyclinic on 18th March 2024 with complain of a lump felt, fatique, constipation and weight loss two month before she had weight gain later without any treatment. She was compomentis, BP 149/90 mmHg, HR 87x/i, Wayne index 0, Billewicz score -22. TSH 93.40 mclU/mL and FT4 0.39 ng/dL, anti-TPO >1000 Iau/mL, TRAb 2.46 IU/L. Thyroid ultrasound showed toxic diffuse struma, thyroid scintigraphy revealed enlarge lobes with high and even distribution and capture of radioactivity with conclusion Toxic Diffuse Struma, and cytologic examination showed colloid goiter. Patient was diagnosed as Hashitoxicosis and has been treated with levothyroxine 100 mg once daily. This woman was diagnosed as Hashitoxicosis based on clinical features of hypothyroidism at admission to polyclinic following clinical features of hyperthyroidism initially without any treatment, with laboratory results showed hypothyroidism with the increased of antibody for Hashimoto Thyroiditis and Grave’s disease. Treatment with levothyroxine 100 mg once daily showed the decrease of TSH and normal FT4 level. We report a case of Hashitoxicosis based on clinical features of hypothyroid following hyperthyroidism initially, laboratory, thyroid ultrasound thyroid scintigraphy, and cytologic examination result. Treatment with levothyroxine showed improvement.